Hatching the Cleidoic Egg: The Role of Thyroid Hormones - De Groef, Bert; Grommen, Sylvia V.; Darras, Veerle M. (Frontiers in Endocrinology, 2013)
A major life stage transition in birds and other oviparous sauropsids is the hatching of the cleidoic egg. Not unlike amphibian metamorphosis, hatching in these species can be regarded as a transition from a relatively well-protected “aqueous” environment to a more hazardous and terrestrial life outside the egg, a transition in which thyroid hormones (often in concert with glucocorticoids) play an important role. In precocial birds such as the chicken, the perihatch period is characterised by peak values of thyroid hormones. Thyroid hormones are implicated in the control of muscle development, lung maturation and the switch from chorioallantoic to pulmonary respiration, yolk sac retraction, gut development and induction of hepatic genes to accommodate the change in dietary energy source, initiation of thermoregulation, and the final stages of brain maturation as well as early posthatch imprinting behavior. There is evidence that, at least for some of these processes, thyroid hormones may have similar roles in non-avian sauropsids. In altricial birds such as passerines on the other hand, thyroid hormones do not rise significantly until well after hatching and peak values coincide with the development of endothermy. It is not known how hatching-associated processes are regulated by hormones in these animals or how this developmental mode evolved from thyroid hormone-dependent precocial hatching.